2022
DOI: 10.1007/s15010-022-01927-3
|View full text |Cite
|
Sign up to set email alerts
|

Infectious encephalitis in elderly patients: a prospective multicentre observational study in France 2016–2019

Abstract: Purpose. Data on encephalitis in the elderly remain scarce. We aimed to describe the characteristics, aetiologies, management, and outcome of encephalitis in patients older than 65 years. Methods.We performed an ancillary study of ENCEIF, a prospective cohort that enrolled all cases of encephalitis managed in 46 clinical sites in France during years 2016-2019. Cases were categorized in 3 age groups: i) 18-64; ii) 65-79; iii) ≥80 years.Results. Of the 494 adults with encephalitis enrolled, 258 (52%) were ≥65 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Additionally, it was found to cause persistent neurological symptoms upon discharge, particularly movement disorders [ 26 ]. A prospective multicentre observational study has shown that viral encephalitis independently predicts 6-month mortality [ 27 ]. This is different from our findings and may be related to the fact that the proportion of encephalitis caused by L. monocytogenes and VZV increased with age, the latter becoming the main cause of infectious encephalitis after 80 years of age, and the proportion of TBE and M. tuberculosis encephalitis decreased with age [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was found to cause persistent neurological symptoms upon discharge, particularly movement disorders [ 26 ]. A prospective multicentre observational study has shown that viral encephalitis independently predicts 6-month mortality [ 27 ]. This is different from our findings and may be related to the fact that the proportion of encephalitis caused by L. monocytogenes and VZV increased with age, the latter becoming the main cause of infectious encephalitis after 80 years of age, and the proportion of TBE and M. tuberculosis encephalitis decreased with age [ 27 ].…”
Section: Discussionmentioning
confidence: 99%